OVERCOMING PSYCHOLOGICAL BARRIERS IN ADULT ENGLISH LANGUAGE LEARNING - Sattarova Dildora Ikramboyevna; Jahongirova Saida Jahongir qizi (TADQIQOTLAR, 2026)
Abstract This article explores the psychological barriers that adult learners face in acquiring English language skills. It delves into common challenges such as fear of failure, lack of confidence, and anxiety, which can hinder progress and motivation. The article emphasizes the importance of understanding these barriers to create supportive learning environments. Strategies for overcoming these obstacles include fostering a growth mindset, building a sense of community among learners, and utilizing positive reinforcement techniques. By addressing psychological factors, educators can enhance the effectiveness of English language instruction for adults, ultimately leading to improved learning outcomes and greater learner satisfaction.